Fenomenologi Komunikasi Organisasi Redaksi Harian Pagi Padang Ekspres dalam Memproduksi Karya Jurnalistik - Wiztian Yoetri; Ilham Firdaus; Emeraldy Chatra; Elva Ronaning Roem (IAI Darussalam, 2021)
This study describes and analyzes the phenomenology of organizational communication carried out in the Communication Organization of the Padang Ekspres Morning Daily Editor in Producing Journalistic Works. This study uses the concept of Phenomenology Theory, where communication experiences between sub-organizations, between individuals, between individuals and groups in the editorial of the Padang Ekspres Morning Daily have experienced a shift in the intensity and climate of communication. This shift was formed due to changes in the ranks of editorial and leadership personnel, this made a fundamental change to the leadership model. If the leadership in the initial management of the establishment that the author ran with the founders was more emphasized on the climate of struggle to establish a newspaper from unknown to well-known and respected, at this time, the editorial crew felt well-known and respected by the public. The trust that has been obtained makes the atmosphere comfortable and far from the spirit of struggle. The atmosphere of a well-established office can be felt when you are in the Padang Ekspres Morning Daily, the facilities are more complete and make the crew work in their minds without feeling that there is tight competition between competitors among newspapers